Курганно-грунтовой могильник золотоордынского времени Золотаревка-3 - Бабенко, В.А. (Степи Европы в эпоху средневековья, 2008)
During the archaeological excavations of barrow 2 of Zolotarievka-3 barrow cemetery on the territory of Ipatovski district of Stavropol province a barrow-ground burial was explored. In total, 30 burials with different states of preservation have been explored; 3 of them were plundered in ancient times, 4 burials were surrounded by small ditches. The remains of burial ground fencing have been discovered in the west and southwest. Burials 9, 10, 16, and 28 surrounded by ring-shape ditches are the earlier ones. Later burials are grouped around the burials with ditches and form irregular rows which extend along the north-northeast – the south-southwest line.